2002
DOI: 10.1073/pnas.012399599
|View full text |Cite
|
Sign up to set email alerts
|

The structural mechanism of GTP stabilized oligomerization and catalytic activation of the Toxoplasma gondii uracil phosphoribosyltransferase

Abstract: Uracil phosphoribosyltransferase (UPRT) is a member of a large family of salvage and biosynthetic enzymes, the phosphoribosyltransferases, and catalyzes the transfer of ribose 5-phosphate from ␣-D-5-phosphoribosyl-1-pyrophosphate (PRPP) to the N1 nitrogen of uracil. The UPRT from the opportunistic pathogen Toxoplasma gondii represents a promising target for rational drug design, because it can create intracellular, lethal nucleotides from subversive substrates. However, the development of such compounds requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 47 publications
1
39
0
3
Order By: Relevance
“…We propose to designate this gene comF despite only moderate sequence identity to the ComF proteins of B. subtilis, H. influenzae, P. stutzeri and S. pneumoniae, used in its identification. The ComF proteins, including Slr0388, harbour a PRT domain, which is a highly conserved region in the PRT family of enzymes involved in the biosynthesis and salvage pathways of purines, pyrimidines and pyridines in bacteria and lower eukaryotes Schumacher et al, 2002). This domain is unique to this family of proteins, and is not found in other PRTases of the tryptophan, histidine and nicotinamide synthetic and salvage pathways (InterPro identifier IPR000836).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose to designate this gene comF despite only moderate sequence identity to the ComF proteins of B. subtilis, H. influenzae, P. stutzeri and S. pneumoniae, used in its identification. The ComF proteins, including Slr0388, harbour a PRT domain, which is a highly conserved region in the PRT family of enzymes involved in the biosynthesis and salvage pathways of purines, pyrimidines and pyridines in bacteria and lower eukaryotes Schumacher et al, 2002). This domain is unique to this family of proteins, and is not found in other PRTases of the tryptophan, histidine and nicotinamide synthetic and salvage pathways (InterPro identifier IPR000836).…”
Section: Discussionmentioning
confidence: 99%
“…adenine) Craig & Eakin, 2000). Apart from this conserved region, the PRT family of enzymes have low sequence similarity, ranging from 20 to 45 % (Schumacher et al, 2002). However, they also possess other regions that confer substrate selectivity and catalytic stability, which may correspond to the conserved region between residues 127 and 147 of the ComF group of proteins ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Kinetic parameters to the naturally occurring substrates, as well as to several important uracil analogs, were determined, and the L. donovani enzyme, unlike its T. gondii counterpart (17), was shown to form a stable tetramer in the absence of GTP. Furthermore, profound substrate inhibition of LdUPRT to nucleobase substrates was demonstrated, providing a mechanism by which L. donovani, T. gondii, T. cruzi, or T. brucei, genetically deficient in pyrimidine biosynthesis, would exhibit a dramatic growth sensitivity to exogenous uracil.…”
mentioning
confidence: 99%
“…The UPRTases from different organisms differ in their regulatory behavior. UPRTase is activated by GTP in several organisms, for example E. coli (Jensen and Mygind 1996), G. intestinalis (Martinussen and Hammer 1994), T. gondii (Schumacher et al 2002), S. shibatae (Linde and Jensen 1996), and S. solfataricus (Jensen et al 2005), whereas its activity seems unregulated in other organisms, for example yeast (Natalini et al 1979) and Bacillus caldolyticus (Kadziola et al 2002). It has been shown that CTP allosterically inhibits S. shibatae (Linde and Jensen 1996), S. solfataricus (Jensen et al 2005), and yeast UPRTase activity whereas UMP, dUMP, dCMP, UDP, TTP, and dCTP allosterically inhibit yeast UPRTase activity (Natalini et al 1979).…”
Section: Introductionmentioning
confidence: 99%
“…By studying the mechanism of activation of UPRTase activity by GTP it was found that UPRTase has two forms, dimeric and tetrameric. The tetrameric form is stabilized by PRPP and/or GTP, both of which contact two dimers of the tetramer; for this reason the stimulatory effect of GTP is seen at subsaturating concentrations of PRPP only (Schumacher et al 2002).…”
Section: Introductionmentioning
confidence: 99%